Spotlight on agroecological cropping practices to improve the resilience of farming systems: a qualitative review of meta-analytic studies - von Cossel, Moritz; Scordia, Danilo; Altieri, Miguel; Gresta, Fabio (Frontiers in Agronomy, 2025)
The capacity of agriculture to withstand or recover from increasing stresses (i.e., resilience) will be continuously challenged by extreme climate change events in the coming decades, altering the growing conditions for crop species. By prioritizing natural processes, agroecology seeks to foster climate change adaptation, boost resilience, and contribute to a low-emission agricultural system. Nineteen different agroecological practices using resilience-related terms and “meta-analysis”, within the subject areas ‘Agriculture and Biological Science’ and ‘Environmental Science’ were addressed, and 34 meta-analyses were reviewed to summarize the state-of-the-art agroecological adaptative strategies applied globally, and the current knowledge gaps on the role of agroecological practices in improving farming system resilience. Two main agroecological strategies stand out: i) crop diversification and ii) ecological soil management. The most frequent diversification practices included agroforestry, intercropping, cover cropping, crop rotation, mixed cropping, mixed farming, and the use of local varieties. Soil management practices included green manure, no-till farming, mulching, and the addition of organic matter. The analyzed studies highlight the complex interplay among soil, plant, climate, management, and socio-economic contexts within the selected agroecological practices. The results varied—positive, null, or negative—depending largely on site-specific factors. Developing and understanding more complex systems in a holistic approach, that integrates plants and animals across multiple trophic levels (feeding relationships, nutrient cycling, and aligning with the principles of a circular economy) is essential. More research is, therefore, needed to understand the interactions between crop diversity and soil management, their impacts on resilience, and how to translate research into practical strategies that farmers can implement effectively.